Duration analysis of factors affecting smoking time: a case study of Türkiye - Selim, Sibel; Sülükçüler, Sevgi (Journal of Dependence, 2023)
Objective: The aim of this study is to analyze the factors affecting the duration of smoking of individuals in Turkey in a comparative way by using the data of the 2012 and 2019 Turkish Health Survey. Method: In this study were used the data of the Turkey Health Survey of 2012 and 2019; in the analyzes 5932 individuals in 2012 and 6833 individuals in 2019 were studied. Factors affecting the duration of smoking of individuals are divided into four basic categories: demographic, socio-economic, chronic diseases and other variables and analyzed with the help of duration analysis. Results: According to the findings of the study, women consume more cigarettes than men in 2012 and 2019. It is seen that the duration of smoking of the participants increased in both years as the education and income level increased. According to the reasons for smoking, it was concluded that for both years, smokers due to curiosity, wannabe, family and personal problems, and friends consumed more time than those who smoked without reason. Conclusion: Based on the findings of both years; in general, it was concluded that the variables of demographic, socioeconomic, chronic diseases and the reason for starting smoking have an effect on the duration of smoking. In addition to the fact that women have a longer smoking time than men, it was observed that the duration of smoking increased as the education and income level increased.